Transfer from inline-skating to alpine skiing learning in physical education - Román, B.; Miranda, M. T.; Martinez, M.; Viciana, J. (Science and Skiing IV, 2009)
INTRODUCTION: Based on the premise that alpine skiing is a risky and technical sport, we studied whether the inline-skating competency practiced in physical education classes, allows for the transfer of similar motor patterns to facilitate the successful, safe and consistent learning of alpine skiing. Schmidt (1988) says that the amount of perceived transfer between two sports disciplines is based on the perception of the similarities between the tasks, while Witherell and Evrard (1993) ensure that inline-skating is the activity that is more closely related to alpine skiing training than any other.